Microneedles for advanced ocular drug delivery - Glover, Katie; Mishra, Deepakkumar; Gade, Shilpkala; Vora, Lalitkumar K.; Wu, Yu; Paredes, Alejandro J.; Donnelly, Ryan F.; Singh, Thakur Raghu Raj (Advanced drug delivery reviews, 2023)
[Display omitted] In the field of ocular drug delivery, topical delivery remains the most common treatment option for managing anterior segment diseases, whileintraocular injectionsare the current gold standard treatment option for treating posterior segment diseases. Nonetheless, topical eye drops are associated with low bioavailability (<5%), and theintravitreal administration procedure is highly invasive, yielding poor patient acceptability. In both cases, frequent administration is currently required. As a result, there is a clear unmet need for sustained drug delivery to the eye, particularly in a manner that can be localised. Microneedles, which are patches containing an array of micron-scale needles (<1 mm), have the potential to meet this need. These platforms can enable localised drug delivery to the eye while enhancing penetration of drug molecules through key ocular barriers, thereby improving overall therapeutic outcomes. Moreover, the minimally invasive manner in which microneedles are applied could provide significant advantages over traditional intravitreal injections regarding patient acceptability. Considering the benefitsofthis novel ocular delivery system, this review provides an in-depth overviewofthe microneedle systems for ocular drug delivery, including the types of microneedles used and therapeutics delivered. Notably, we outline and discuss the current challenges associated with the clinical translation of these platforms and offer opinions on factors which should be considered to improve such transition from lab to clinic.